2022
DOI: 10.2147/jmdh.s353168
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nature-Based Intervention in Occupational Health Care on Stress – A Finnish Pilot Study Comparing Stress Evaluation Methods

Abstract: Purpose To assess methodology and its limitations for measuring effects of nature-based intervention (NBI). Patients and Methods Participants were 11 middle-aged female health care workers with lowered capacity to work. NBI included six group appointments in six months study period. Heart rate variability (HRV) and self-reported pain and work exhaustion were measured pre-post study period. Salivary α-amylase samples were collected immediately before and after three indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 58 publications
0
11
0
1
Order By: Relevance
“…There were seven different types of outdoor intervention; however, over half of the studies were one-day forest therapy interventions [14,16,[28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44]. Other studies included mountaineering expeditions [41][42][43][44], forest therapy camps [45][46][47][48], green exercise [49][50][51][52], blue exercise [53], horseback riding [54], and skydiving [55]. Over half of the control groups had a similar exposure type as the intervention but in an urban context.…”
Section: Methods Characteristicsmentioning
confidence: 99%
See 4 more Smart Citations
“…There were seven different types of outdoor intervention; however, over half of the studies were one-day forest therapy interventions [14,16,[28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44]. Other studies included mountaineering expeditions [41][42][43][44], forest therapy camps [45][46][47][48], green exercise [49][50][51][52], blue exercise [53], horseback riding [54], and skydiving [55]. Over half of the control groups had a similar exposure type as the intervention but in an urban context.…”
Section: Methods Characteristicsmentioning
confidence: 99%
“…Table 4 summarizes the characteristics of HRV analysis methods used in the 34 empirical studies. Seventeen studies reported the HRV measurement period to be during the intervention [34,[36][37][38][39][40][41]43,44,48,49,51,53,54,58], and 17 studies reported the measurement period as pre-post-intervention [28,31,33,35,[45][46][47]49,50,52,[54][55][56][57]60,62]. Interventions had a wide range of exposure times, ranging from six minutes [40] up to eighty days [45].…”
Section: Hrv Analysis Methods Usedmentioning
confidence: 99%
See 3 more Smart Citations